Network disruption detected in LY (Libya) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Libya. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: LY-2026-0001. Severity: critical. Confidence: 70%